Volume 2A: Turbomachinery 2016
DOI: 10.1115/gt2016-57372
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rotor Tip Flow Field Mis-Prediction on Rotating Disturbance Near Surge in a High Speed Multistage Compressor

Abstract: In this work, unsteady numerical results and high-frequency measurements are investigated from nominal to loaded operating points with the objective to contribute to the understanding of pre-stall rotating disturbances. A 3.5 stages high speed axial multistage compressor is investigated on a 2 MW test rig in the laboratory of fluid mechanics (LMFA) at Ecole Centrale de Lyon, France. The compressor has been built by Snecma, and is representative of modern high-pressure rear blocks of a modern aircraft engine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The radial locations in the computation match the positions of experimental probes. In addition to the uncertainties in measurement chains, Schreiber et al [48] have recently quantified some discrepancies between experimental and existing numerical studies of CREATE. First, the geometry of the computational domain is simplified as it accounts neither for leakages at hub and casing between each row, except below S1, nor for hub and tip clearances of IGVs.…”
Section: Computational Cost and Convergence Of The Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radial locations in the computation match the positions of experimental probes. In addition to the uncertainties in measurement chains, Schreiber et al [48] have recently quantified some discrepancies between experimental and existing numerical studies of CREATE. First, the geometry of the computational domain is simplified as it accounts neither for leakages at hub and casing between each row, except below S1, nor for hub and tip clearances of IGVs.…”
Section: Computational Cost and Convergence Of The Simulationsmentioning
confidence: 99%
“…URANS simulations of CREATE have been assessed against experimental data [38,5] allowing to study a casing treatment for control of tip leakage flows [17]. Crevel et al [6] and Schreiber et al [48] performed URANS simulations at low mass flow rate for instability investigation, even simulating a full surge cycle [7]. However some limitations in the application of URANS to axial compressors could be evidenced.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the plenums located upstream and downstream the compressor need to be accounted for to simulate a full surge cycle. Recently, on a different version of CREATE, the URANS simulation of Schreiber et al (2016) showed 32 rotating instabilities at 72% of shaft speed at a low mass flow rate operating point. All these simulations were performed over an azimuthal sector of the compressor, hence enforcing the amount of instabilities to be a multiple of the circumferential periodicity.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently one temporal period corresponds to 1/16th of a rotor revolution. A profound knowledge-base has been acquired with CREATE for numerical and experimental methods aiming at flow field investigations in the high-speed multistage compressor environment [10][11][12][13]. Standard tip gap sizes are implemented compared to increased tip gaps in rotors 2 and 3 in the previous version of CREATE.…”
Section: Test Case (Create)mentioning
confidence: 99%